2016
DOI: 10.1016/j.urology.2015.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physiotherapy in the Treatment of Neurogenic Bladder in Patients Infected With Human T-Lymphotropic Virus 1

Abstract: Objective To evaluate the efficacy of physiotherapy for urinary manifestations in patients with HTLV-1-associated lower urinary tract dysfunction. Methods Open clinical trial with 21 patients attending the physiotherapy clinic of the Hospital Universitário, Bahia, Brazil. Combinations of behavioral therapy, perineal exercises and intravaginal/intra-anal electrical stimulation were used. Results The mean age was 54±12 years and 67% were female. After treatment, there was an improvement in symptoms of urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
0
9
0
10
Order By: Relevance
“…The movement therapy program included the electrical stimulation of the pelvic floor muscles. The results showed that physiotherapy was effective in reducing symptoms, increasing perineal muscle strength, and improving urodynamic parameters and quality of life [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…The movement therapy program included the electrical stimulation of the pelvic floor muscles. The results showed that physiotherapy was effective in reducing symptoms, increasing perineal muscle strength, and improving urodynamic parameters and quality of life [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…As for the physical therapy resources used in the treatment, the use of individual outpatient kinesiotherapy was identified through functional exercises 36,37,38,39, home exercises 40 , proprioceptive neuromuscular facilitation 41,42 , Pilates 43,44 , virtual reality 45,46 , respiratory training 47 , electrical stimulation 48,39 , neuromodulation with tDCS 49 and rTMS 29 . Most of these resources have no side effects, are low cost, help to delay the evolution of dysfunctions and have a positive impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrou que a eletroterapia no miôtomo de S4 com parâmetro de 12 Hz foi eficiente para promoção da redução dos sintomas de hiperatividade detrusora avaliados pelo OABv8 e incremento dos parâmetros de contratilidade e força do assoalho pélvico pelo esquema PERFECT, além de melhora dos parâmetros urodinâmicos. O que proporcionou redução de urge incontinência e melhora qualidade de vida das participantes [30].…”
Section: Discussionunclassified